Host Gene SEL1L Involved in Endoplasmic Reticulum-Associated Degradation Pathway Could Inhibit Hepatitis B Virus at RNA, DNA, and Protein Levels - Wang, Jinyu; Li, Jing; Wu, Jingwen; Dong, Minhui; Shen, Zhongliang; Lin, Yong; Li, Fahong; Zhang, Yongmei; Mao, Richeng; Lu, Mengji; Zhang, Jiming (Frontiers in Microbiology, 2019)
Hepatitis B virus (HBV) belongs to the Hepadnaviridae family of enveloped DNA viruses. Recent studies have demonstrated that host factors can suppress HBV replication. HBV envelope proteins are reported to be degraded by the endoplasmic reticulum-associated degradation (ERAD) pathway. As a component of the ERAD pathway, suppressor of lin-12-like 1 (SEL1L) was earlier found to be up regulated in the inactive carrier phase of chronic HBV infection relative to that in the immune tolerant phase. However, the role of SEL1L in regulating HBV replication remains largely unknown. In the present study, we found the levels of HBV RNA, DNA, and core and envelope proteins to be significantly down-regulated by SEL1L overexpression, and up regulated by SEL1L silencing, in Huh7 cells transiently transfected with an overlength HBV genome. Similar up regulation was observed in HepG2.2.15 cells as well. SEL1L co-localized with HBV s antigen (HBsAg), which changed its staining pattern. Treatment with an inhibitor of ERAD pathway remarkably increased intracellular S protein. Surprisingly, silencing SEL1L to block the ERAD pathway activated an alternative ER quality control (ERQC)-autophagy pathway, which might account for the increased HBV RNAs and core protein. Together, our results demonstrate that SEL1L is a host restriction factor that exerts anti-HBV effect through ERAD and alternative ERQC-autophagy pathway.